Hydrocarbon Content of the Manitoulin Dolomite on Manitoulin Island - Cameron, John A. (My University, 1975)
The Manitoulin Formation on Manitoulin Island consists of a lower biostrome extending across the island and an upper biohermal accumulation just south of Manitowaning.
Viscible hydrocarbon accumulations occur in the bioherm, mostly contained in the more porous framework corals Paleofavosites and Palaeophyllum. Hydrocarbons found in other sample sites across the island show a very low bulk weight per cent and are of no economic significance.
The bulk of the hydrocarbon was likely formed in lower carbonates near the centre of the Michigan Basin. Petroleum is also thought to have been introduced with solutions which formed calcite deposits.
Keywords: geology; hydrocarbon; Manitoulin, island; dolomite